Agency and facial emotion judgment in context - Ito, Kenichi (2013)
Past research showed that East Asians’ belief in holism was expressed as their tendencies to include background facial emotions into the evaluation of target faces more than North Americans. However, this pattern can be interpreted as North Americans’ tendency to downplay background facial emotions due to their conceptualization of facial emotion as volitional expression of internal states. Examining this alternative explanation, we investigated whether different types of contextual information produce varying degrees of effect on one’s face evaluation across cultures. In three studies, European Canadians and East Asians rated the intensity of target facial emotions surrounded with either affectively salient landscape sceneries or background facial emotions. The results showed that, although affectively salient landscapes influenced the judgment of both cultural groups, only European Canadians downplayed the background facial emotions. The role of agency as differently conceptualized across cultures and multilayered systems of cultural meanings are discussed.